2018
DOI: 10.1371/journal.pone.0191872
|View full text |Cite
|
Sign up to set email alerts
|

A novel monoclonal antibody targeting carboxymethyllysine, an advanced glycation end product in atherosclerosis and pancreatic cancer

Abstract: Advanced glycation end products are formed by non-enzymatic reactions between proteins and carbohydrates, causing irreversible lysine and arginine alterations that severely affect protein structure and function. The resulting modifications induce inflammation by binding to scavenger receptors. An increase in advanced glycation end products is observed in a number of diseases e.g. atherosclerosis and cancer. Since advanced glycation end products also are present in healthy individuals, their detection and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Recent evidence has also revealed that the antibody targeting of RAGE ligands such as HMGB1 and AGEs may effectively decrease tumor progression in solid malignancies[ 74 ]. This approach can even enhance the antitumoral response of cancer immunotherapies by remobilizing the antitumor immune response[ 75 ].…”
Section: Therapeutic Potential Of the Rage/ages Axis In Tumor Biologymentioning
confidence: 99%
“…Recent evidence has also revealed that the antibody targeting of RAGE ligands such as HMGB1 and AGEs may effectively decrease tumor progression in solid malignancies[ 74 ]. This approach can even enhance the antitumoral response of cancer immunotherapies by remobilizing the antitumor immune response[ 75 ].…”
Section: Therapeutic Potential Of the Rage/ages Axis In Tumor Biologymentioning
confidence: 99%
“…AGEs have been observed not only in diseases such as atherosclerosis, rheumatoid arthritis, Alzheimer's disease and diabetes but various forms of cancer [35]. People with diabetes are at a significantly higher risk of many forms of cancer according to epidemiologic evidence.…”
Section: Age and Cancermentioning
confidence: 99%
“…However, methods based on the detection of autofluorescence of AGEs are limited as they exclusively measure the total fluorescent glycation. New promising methodologies for high-throughput generation of monoclonal antibodies mapped with epitopes against AGE have been applied and validated [26,27]. Signs of progress have been obtained in identifying epitopes, reaching a high level of sensitivity and a simple analytical procedure [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…New promising methodologies for high-throughput generation of monoclonal antibodies mapped with epitopes against AGE have been applied and validated [26,27]. Signs of progress have been obtained in identifying epitopes, reaching a high level of sensitivity and a simple analytical procedure [26,27]. However, improvements in cultivation techniques and in the construction of specific monoclonal epitopes represent important goals to be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation